Enhancement of Mechanical and Thermal Properties of Poly(L-lactide) Nanocomposites Filled with Synthetic Layered Compounds - Telma Nogueira Caio; Núria Gonçalves; Fernando Wypych; Liliane Maria Ferrareso Lona (International Journal of Polymer Science)
The effects of a layered double hydroxide (LDH) (Zn/Al palmitate) and two layered hydroxide salts (LHS), intercalated with the anion salicylate or palmitate, on the properties of poly(L-lactide) (PLLA) nanocomposites were investigated. PLLA and the nanocomposites were synthesized by ring opening polymerization of the cyclic dimer of lactic acid (lactide), using tin(II) 2-ethylhexanoate (stannous octanoate) as catalyst. PLLA nanocomposites containing two different fillers concentrations (1 wt% and 2 wt%) were produced. Compared to PLLA, almost all the nanocomposites exhibited an enhancement on thermal resistance. The sample containing 1 wt% of Zn/Al palmitate exhibited a decomposition temperature 51°C higher than neat polymer. Results of flexural properties demonstrated that the nanocomposites containing Zn/Al palmitate displayed the highest values of maximum flexural stress and elongation at break. The sample with 2 wt% of this filler revealed values of maximum flexural stress and strain at break, 15% and 157%, respectively, higher than PLLA. Contrary to PLLA, which only exhibited break point, this nanocomposite showed a less fragile behavior, as a yield point was observed. In this case, it was possible to promote a higher flexibility without reducing the flexural stress, revealing an advantage of the Zn/Al palmitate under the plasticizers that have been used so far for PLLA.